Biological Pathways as Substantiation of the Use of Copper Radioisotopes in Cancer Theranostics - Niculae, Dana; Dusman, Ramona; Leonte, Radu A.; Chilug, Livia E.; Dragoi, Cristina M.; Nicolae, Alina; Serban, Radu M.; Niculae, Dragos A.; Dumitrescu, Ion B.; Draganescu, Doina (Frontiers in Physics, 2021)
Copper, a cofactor for many enzymes, is a bioelement that is involved in many main biochemical processes; although high levels of copper promote the proliferation of cancer cells. Further development of radiopharmaceuticals based on copper radioisotopes depend on understanding and taking advantage of its biochemical pathways in oncogenesis. As with other radiometals used in molecular imaging and/or targeted therapy, biological vectors are employed to transport copper radioisotopes to a target, aiming for high specific uptake at tumor sites and precise delivery of ionizing radiation. Evidence of the clinical utility of copper radioisotopes in the ionic form CuCl2 were also proven in an in vivo study of the copper metabolism, guiding personalized copper-chelating treatment in cancer patients and in imaging pathological sites associated with copper imbalance. Five of the copper radioisotopes have gained interest for nuclear medicine applications, based on their emissions, energies, and half-lives, as they can be produced with pharmaceutical-grade quality. The uptake mechanism, kinetics, and metabolic parameters are important findings in molecular imaging, which are decisive when designing individualized targeted radiotherapy for dose calculations of high linear energy transfer Auger electrons and β− emissions of 64Cu and 67Cu. As radiation deposits a high amount of energy within the intra-cellular space, the biochemical involvement of copper determines targets in drug design and validation. The biochemical pathways depict copper metabolism in normal cells and highlight its increased activity in tumor progression and angiogenesis. The avid uptake of copper into inter- and intra-mitochondrial spaces, as constituents of cytochrome C oxidase, substantiate the selection of 64/67CuCl2 as theranostic agents.